(untitled) (Global Journals of Research in Engineering, 2024)
This study investigates black oil s pressure volume and temperature PVT properties from well X analyzed using subsurface and surface recombination samples Black oil samples were collected from the Q oil field and subjected to PVT analysis at the Reservoir Fluid Laboratory in Port Harcourt Key findings include bubble point pressure Pb of 2000 psi with a standing correlation value of 1934 3 psi resulting in a 3 3 difference The solution gas oil ratio was measured at 647 3 SCF STB compared to 671 0 SCF STB from correlations a difference of 3 5 The oil formation volume factor Bo was 1 456 res Bbl STB while standing correlations indicated 1 0675 res Bbl STB showing a 3 6 difference The isothermal compressibility ranged from 10 12 x 10 sup -6 sup psi sup -1 sup at 4500 psi to 4 1309 x 10 sup 18 sup cp at 15 psi Gas evolution began at 2000 psig and increased with decreasing pressure Viscosity varied significantly recorded at 0 54 cp at 4500 psig and 1 38 cp at 15 psig The reservoir contains heavy crude oil with an API rating of 30 and an average absolute error of 3 5 0 035 These results enhance reservoir characterization and validate the use of PVT calculations in analyzing volatile black oil samples